Changes in health communication in the age of COVID-19: A study on the dissemination of preprints to the public - Zeng, Li (Frontiers in Public Health, 2023)
Preprints have become an important tool for meeting the challenges of health communication in the context of COVID-19. They allow scientists to disseminate their results more quickly due to the absence of a peer review process. Preprints have been well received by scientists, however, there have been concerns about the exposure of wider public audiences to preprints due in part to this lack of peer review. The aim of this study is to examine the dissemination of preprints on medRxiv and bioRxiv during the COVID-19 pandemic using content analysis and statistical analysis. Our findings show that preprints have played an unprecedented role in disseminating COVID-19-related science results to the public. While the overall media coverage of preprints is unsatisfactory, digital native news media performed better than legacy media in reporting preprints,which means that we could make the most of digital native media to improve health communication.This study contributes to understanding how science communication has evolved in response to the COVID-19 pandemic and provides some practical recommendations.